THE INFLUENCE OF INNOVATION, PROMOTION AND SERVICE QUALITY ON PRODUCT PURCHASE DECISIONS IN TRULY CAFE AND RESTO BENGKULU - Deny Triwijaya ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2021)
The study aimed to determine the effect of Innovation, Promotion, and Service Quality on Purchasing Decisions of Products in Truly Cafe and Resto Bengkulu and to find out which factors were the most dominant affecting purchasing decisions. This study employed a descriptive quantitative research method. The population in this study were all consumers in Bengkulu Cafe and Resto Truly and samples taken amounting to 96 people and sampling using the accidental sampling method. Data collection method was through using the questionnaire method. Based on the results of multiple linear regression obtained by the regression equation Y = 1,692 + 0.580 (X_1) + 0.968 (X2) + 0.217 (X3). The results of the study and the hypothesis indicate that innovation (sig Î± = 0,000 <0.050), promotion (sig Î± = 0,000 <0.050), service quality (sig Î± = 0.031 <0.050). The results showed that there was an impact between the Innovation (X1), Promotion (X2), and Service Quality (X3) variables significantly on the Purchasing Decision (Y) on the On July Cafe and Resto Bengkulu. To be better, it needs to be improved again such as multiplying to follow the trends that occur and pay attention to the quality and quality of good work and others in order to increase the Purchasing Decisions in Truly Cafe and Resto Bengkulu.Â Keywords: Innovation, Promotion, Service Quality, Purchasing Decisions